Answer:
<u><em>F(x)= 5*[
+ (a*b)*
+ a*b*x + C.</em></u>
Step-by-step explanation:
<u><em>First step we aplicate distributive property to the function.</em></u>
<u><em>5*(x+a)*(x+b)= 5*[
+x*b+a*x+a*b]</em></u>
<u><em>5*[
+x*(b+a)+a*b]= f(x), where a, b are constant and a≠b</em></u>
<u><em>integrating we find ⇒∫f(x)*dx= F(x) + C, where C= integration´s constant</em></u>
<u><em>∫^5*[
+x*(a+b)+a*b]*dx, apply integral´s property</em></u>
<u><em>5*[∫
dx+∫(a*b)*x*dx + ∫a*b*dx], resolving the integrals </em></u>
<u><em>5*[
+ (a*b)*
+ a*b*x</em></u>
<u><em>Finally we can write the function F(x)</em></u>
<u><em>F(x)= 5*[
+ (a*b)*
+ a*b*x ]+ C.</em></u>